KEPUASAN MAHASISWA TERHADAP PELAYANAN PERPUSTAKAAN DI LINGKUNGAN UNIVERSITAS LANCANG KUNING TAHUN 2016 - Amelia, Vita; Hakim, Triono Dul (Jurnal Ilmu Budaya, 2017)
Unilak’s library contains a collection of reference books, research journals, documents and other important information which support the learning process for students. As the information resource, it needs to complete its facilities such as books collection. The library keeps increasing the numbers of books but not all of them are needed by the users. Besides, the library should provide good service from the librarians in order it can satisfy the users. Comfort is another element which may determine the users’ spending time in the library. Thus, the library management needs to evaluate its service. Related to that, this study is conducted to identify the level of satisfaction of the users towards the service provided by Unilak’s library management. Moreover, it is done to show which facilities are priority to be paid attention as well as for the reference of the policy makers to decide for better development.